The Islamic Economic Law Perspective on Sharia Mutual Fund Investment - Risfiana Mayangsari (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2020)
Abstract: The tendency of Indonesian people to invest, which has recently been increasing, has made these people more selective in determining their investment choices and goals. One of the choices of Indonesian people in investing is sharia mutual funds. Because fundamentally sharia mutual fund investment does not violate the boundaries of sharia and remains in the corridor of Islam, thus investment activity is a form of muamalah (civil) activity in Islam. So, this article aims to explain Islamic mutual fund investment in the perspective of Islamic economic law. This article is based on library research; the data in this study is documentary data in the form of books, articles and notes related to the theme of Islamic mutual funds investment in the perspective of Islamic economic law. So, the conclusion is that Islamic mutual funds in the management and investment policies refer to Islamic law. Regulations for sharia mutual funds in Indonesia are contained in positive law, both conventional and those based on sharia principles are the same, namely regulated in Law No. 8 of 1995 concerning the Capital Market and technical regulations in the form of Government Regulations, Decree of the Minister of Finance, and regulations issued by Bapepam and regulations issued by the Stock Exchange as Self Organitation Regulatory, Fatwa of the National Sharia Council No.20 / DSN-MUI / IV / 2001 regarding Islamic mutual funds. Keywords: Investment, mutual funds, sharia law. Abstrak: Kecendrungan masyarakat Indonesia dalam berinvestasi yang akhir-akhir ini semakin meningkat, menjadikan masyarakat tersebut lebih selektif dalam menentukan pilihan dan tujuan berinvestasi. Salah satu pilihan masyarakat Indonesia dalam berinvestasi adalah reksadana syariah. Karena, secara fundamental investasi reksadana syariah tidak melanggar batasan syariah dan tetap pada koridor Islam, sehingga dengan demikian kegiatan investasi tersebut merupakan bentuk kegiatan muamalah (keperdataan) dalam Islam. Maka artikel ini bertujuan untuk menjelaskan investasi reksadana syariah daam perspektif hukum ekonomi syariah. Artikel ini berbasis penelitian pustaka, data dalam penelitian ini adalah data dokumentasi berupaka buku-buku, artikel, dan catatan-catatan yang berhubungan dengan tema investasi reksadana syariah dalam perspektif hukum ekonomi syariah. Maka, kesimpulnnya adalah reksadana syariah dalam pengelolaan dan kebijakan investasinya mengacu pada syariat Islam. Pengaturan reksadana syariah di Indonesia tertuang dalam hukum positif, baik yang konvensional maupun yang berdasarkan Prinsip syariah adalah sama yaitu diatur dalam Undang-Undang No. 8 Tahun 1995 tentang Pasar Modal dan peraturan teknis berupa Peraturan Pemerintah, Keputusan Menteri Keuangan, dan peraturan-peraturan yang dikeluarkan oleh Bapepam dan peraturan-peraturan yang dikeluarkan oleh Bursa Efek selaku Self Organitation Regulatory, Fatwa Dewan Syariah Nasional No.20/DSN-MUI/IV/2001 tentang reksadana syariah. Kata-kata kunci: Investasi, reksadana, hukum syariah.